Respuesta :
Just plug in one of the other (doesn't matter which one) so it will look like
-3x+6=5x+38
or
5x+38=-3x+6 (it's the same thing as the first one)
Then you solve for x and you substitute that value so you can get y.
Hope this helped :)
-3x+6=5x+38
or
5x+38=-3x+6 (it's the same thing as the first one)
Then you solve for x and you substitute that value so you can get y.
Hope this helped :)
you will equalize the two equations of y so
-3x+6=5x+38
5x+3x=38-6
8x=32
x=4
then you will substitute in the equation of y
-3x+6=5x+38
5x+3x=38-6
8x=32
x=4
then you will substitute in the equation of y